PENGARUH KREATIVITAS MENGAJAR GURU DAN MOTIVASI BELAJAR SISWA TERHADAP KEMAMPUAN MENGHAFAL SISWA DI SD IT AN-NIDA KOTA LUBUKLINGGAU - Niah Elfita Sari (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2018)
This study  aims to determine the influence  of teacher  teaching  creativity on the students  ‘ability to memorize  Al- Qur’an,  to determine the effect of students’  learning  motivation on the students  ‘ability to memorize  Al-Qur’an to know the influence  of teacher’s  teaching  creativity and  student’s  learning  motivation to students’  ability to memorize  Al- Qur’an.  The population of this research  is the students  of class VI A and  VI B which amounted to 240  people,  while the samples  in this study is 25% of the population of 60 people.  Based  on the discussion of research  results that the influence of teacher  teaching creativity and students’ learning motivation to the ability to memorize grade 6 students of SD IT AN-NIDA of Lubuklinggau  City in 2017,  can be summarized as follows: First, there is a significant influence between  teachers’  teaching  creativity on students’ memorization ability. This is based  on the calculation  of the correlation  between  X1 to Y of 0.581  and  regression  equation Y= 26.619 +0.581. Second, there  is a significant influence  between  students’  learning  motivation on the ability to memorize students.  This is based  on the calculation  of the correlation  between  X2 to Y of 0.033  and  regression  equation Y = 8.258  +0.033.  Third, there  is a very significant influence  between  teacher  teaching  creativity and  student  learning  motivation jointly or individually  to the ability to memorize  students.  From result of correlation  calculation  by using multiple regression  analysis obtained correlation  price of R between  X1 and X2 together  to Y equal to 0,583  and regression  equation Y = 14,684 + 0,587= 0,045.